Militere verset teen Britse bestuur : die eerste Vryheidsoorlog, 1880-1881 (Historia, 2021)
-
Keywords: Military revolt; Kruger, S.P.J.; Pretoria Convention; History; Pretorius, M.W.; Freedom War I; South African Republic; Paardekraal meeting; Natal Field Force; Anglo-Boer War I; Zuid-Afrikaansche Republic; Battle of Laingsnek; Pomeroy-Colley, G. Sir; Battle of Majuba; Joubert, P.J.